An air-stable organometallic polymer containing titanafluorene moieties obtained by the Sonogashira–Hagihara cross-coupling polycondensation. Issue 8 (11th February 2021) - Tanudjaja, Alvin; Inagi, Shinsuke; Kitamura, Fusao; Takata, Toshikazu; Tomita, Ikuyoshi
Abstract : A stable fused titanacycle-containing polymer is synthesized and its properties are described. Abstract : The synthesis of a polymer containing alternating titanafluorene and arylene ethynylene moieties is described. The polymerization of a 2, 7-dibromo-9-titanafluorene derivative with 1, 4-dioctyloxy-2, 5-diethynylbenzene is carried out at 70 °C for 48 h in tetrahydrofuran (THF) in the presence of palladium dichloride/4, 5-bis(diphenylphosphino)-9, 9-dimethylxanthene as a catalyst and diisopropylamine as a base to produce a dark red polymer. The polymer thus obtained is soluble in organic solvents and stable towards both air and moisture. In the UV-vis absorption spectrum of the polymer, the absorption maxima ( λ max ) are observed at 321 nm and 395 nm, which are bathochromically shifted compared to those of a model compound of the repeating unit, a 2, 7-bis(phenylethynyl)titanafluorene derivative ( λ max = 309 nm and 364 nm). The optical band gap ( E g ) of the polymer is estimated to be 2.8 eV on the basis of the absorption onset, which is narrower than that of the model compound (3.1 eV).